Exploration of Ethnomathematics in the Traditional House of Sonaf Maubes-Insana - Maria Fransiska Tas’au; Aloisius Loka Son; Talisadika S. Maifa (Indonesian Educational Research Journal, 2023)
The purpose of this study is (1) to explore the mathematical concepts contained in the sonaf-maubes traditional house, and (2) to find out the symbolic meaning contained in the sonaf maubes traditional house. The type of research used is qualitative research with an ethnographic approach. The subjects in this study were people who could provide explanatory information about something that would be examined, including traditional leaders, guardians of the sonaf maubes traditional house and builders as well as the people of the Usfinit tribe who provided information about the history of the sonaf maubes traditional house. Data collection techniques used are interviews, observation, and documentation. Based on the results of the research, it can be concluded that (1) there are mathematical concepts found in the Sonaf-Maubes traditional house, namely flat shapes, spatial shapes, line concepts, counting concepts, distance concepts, and reflections (reflection), (2) there are symbolic meanings in the Sonaf-Maubes traditional houses on the traditional stone pillar main, roof, attic, doors, stoves and so on